MONITORING PERUBAHAN GARIS PANTAI DI KOTA PADANG PERIODE TAHUN 1988 – 2018 MENGGUNAKAN CITRA LANDSAT - Yulia Nanda; febriandi febriandi (JURNAL BUANA, 2020)
The purpose of this research is to monitor shoreline changes in Padang city in the period 1988 to 2018. The monitoring carried out was to find out the dynamics of shoreline changes and the factors causing shoreline changes, as well as changes in land cover affected by shoreline changes. This type of research is quantitative descriptive. The analysis method is remote sensing and geographic information systems. The results showed the coastline in Padang had changed from year to year. Changes occur in the form of accretion and abrasion. In the period 1988 to 1998, the beach in Padang experienced abrasion by 47,90 ha. In the period 1998 to 2008, the coast in Padang experienced an accretion of 79,37 ha. In the period 2008 to 2018, the beach in Padang also experienced accretion by 61,84 ha. Abrasion and accretion that occurs is caused by oceanographic factors such as wind and waves. Abrasion in the period 1988 to 1998 resulted in changes with an increased land cover reduction by 13 ha. Accretion in the period 1998 to 2008 resulted in changes with an increased land cover by 63,82 ha. Accretion in the period 2008 to 2018 resulted in changes with increased land cover by 43,95 ha.